Changes in the viability of Strongyloides ransomi larvae (Nematoda, Rhabditida) under the influence of synthetic flavourings - Boyko, Oleksandra; Бойко, Олександра Олександрівна; Brygadyrenko, Victor; Бригадиренко, Віктор Васильович (Дніпропетровський національний університет ім. О.Гончара, 2017)
One of the most common nematodes of pigs globally is Strongyloides ransomi Schwartz and Alicata 1930. It usually causes aggravation of physiological indicators of its hosts and damage to their immune system. Also it is a good modelling object for the evaluation of the antiparasitic activity of new antihelminthic drugs. We conducted laboratory experiments to assess the effect of flavouring additives with flower odour (benzaldehyde, citral, D-limonene and β-ionone) upon the viability of S. ransomi larvae. The mortality rate was calculated for 24 hours exposure at four concentrations of each substance (10, 1, 0.1 и 0.01 g/l) with eight replications. The lowest LD50 values were obtained for citral (97 mg/l) and benzaldehyde (142 mg/l). These substances are recommended for further evaluation of their antihelminthic effect in experiments using laboratory animals. Unlike other substances, the effect of β-ionone and D-limonene even at a concentration of 10 g/l after 24 hours caused the death of <50% of S. ransomi larvae. The study of flavouring additives with flowery odour, which are permitted to be used in food for humans and also to be used in cosmetics, is a promising field for research aimed at the development of new antiparasitic drugs. Однією з найпоширеніших нематод свиней в усьому світі є Strongyloides ransomi Schwartz та Alicata 1930. Вона зазвичай викликає загострення фізіологічних показників її хазяїв та пошкодження їх імунної системи. Також це хороший об'єкт моделювання для оцінки антипаразитарної активності нових антигельмінтних препаратів. Ми провели лабораторні експерименти з оцінки впливу ароматичних добавок з квітковим запахом (бензальдегід, цитрал, D-лімонен і β-іонону) на життєздатність личинок S. ransomi. Рівень смертності був розрахований через 24 години експозиції в чотирьох концентраціях кожного речовини (10, 1, 0,1 і 0,01 г / л) у восьмикратній повторності. Найнижчі значення LD50 були отримані для цитралю (97 мг / л) і бензальдегіду (142 мг / л). Ці речовини рекомендовані для подальшої оцінки їх антигельмінтного ефекту в експериментах з використанням лабораторних тварин. На відміну від інших речовин, вплив бетта-іонону і Д-лімонен навіть при концентрації 10 г / л через 24 години викликав загибель <50% личинок S. ransomi. Вивчення ароматичних добавок з квітковим запахом, які дозволені для використання в їжу людини, а також для використання в косметології, є перспективним напрямком для досліджень, спрямованих на розробку нових антипаразитарних препаратів.
Зміна життєздатності личинок Strongyloides ransomi (Nematoda, Rhabditida) під впливом синтетичних ароматизаторів
Keywords: Nematoda; нематоди; antiparasitic activity; протипаразитарна активність; benzaldehyde; бензальдегід; D-limonene; Д-лімонен; flavouring agents; ароматизатори; citral; цитраль; L-linalool; Л-ліналоол; β-ionone; бетта-іонон